Aggregation and Model Construction for Volatility Models. - Barndorff-Nielsen, O; Shephard, N (Nuffield College (University of Oxford), 1998)
In this paper we will rigourously study some of the properties of continuous time stochastic volatility models. We have five main results, including: the stochastic volatility class can be linked to Cox process based models of tick-by-tick financial data; we characterise the moments, autocorrelation function and spectrum of squared returns; based only on discrete time returns, we give a simple consistent and asymptotically normally distributed estimator of continuous time volatility models without any simulation or discretisation error.